2013
DOI: 10.1007/s10964-013-9914-8
|View full text |Cite
|
Sign up to set email alerts
|

Dating Violence, Bullying, and Sexual Harassment: Longitudinal Profiles and Transitions Over Time

Abstract: Although there is growing recognition of the problem of dating violence, little is known about how it unfolds among young adolescents who are just beginning to date. This study examined classes (subgroups) and transitions between classes over three time points based on dating violence, bullying, and sexual harassment perpetration and victimization experienced by youth. The sample was ethnically diverse, consisting of 795 seventh-grade students from schools that were part of a multi-site, longitudinal evaluatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
86
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(94 citation statements)
references
References 36 publications
5
86
1
2
Order By: Relevance
“…Different from Miller et al (2013), current results did not indicate any gender differences in bullying perpetration to support the assertion that aggressive behavior is less stable among girls than boys. However, we found that girls were more likely to experience verbal/relational and cyber victimization than boys, and boys were more likely to be physi cally victimized.…”
Section: Changes In Bullying Behaviors and Victimizationcontrasting
confidence: 54%
“…Different from Miller et al (2013), current results did not indicate any gender differences in bullying perpetration to support the assertion that aggressive behavior is less stable among girls than boys. However, we found that girls were more likely to experience verbal/relational and cyber victimization than boys, and boys were more likely to be physi cally victimized.…”
Section: Changes In Bullying Behaviors and Victimizationcontrasting
confidence: 54%
“…Also, in the 7th grade curriculum, youth learn how sexual harassment differs from flirting, their school's sexual harassment policy, and learn assertive skills to refuse sexual harassment. This is a critical component of the SS-SSTP given research documenting that bully perpetration is a precursor to the development of sexual harassment among middle school youth (Espelage, Basile, & Hamburger, 2012;Miller et al, 2013). Further, this sexual harassment takes the form of directing homophobic epithets toward other peers, which provides support for assessing the use of homophobic epithets in this study (Espelage, Basile, De La Rue, & Hamburger, in press).…”
Section: Bullying and Sexual Harassment Preventionmentioning
confidence: 52%
“…These findings are critical given the recent research demonstrating that homophobic name-calling and sexual violence are emerging as significant public health concerns and are precursors to teen dating violence Miller et al, 2013). About half of the students in 7th through 12th grades were the victims of sexual harassment at school during the 2010-11 school year, with 56% of females and 40% of males experiencing sexual harassment in person or online (AAUW, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…For example, by high school 10 % of youth have experienced physical dating violence victimization (Miller et al 2013). In turn, research has indicated that youth involved in bullying are more likely to experience teen dating violence (Debnam et al 2016;Holt et al 2007).…”
Section: Conceptualization Of Bullying In Adolescence and Relevance Omentioning
confidence: 99%